Spinal Anaesthesia as an Adjunct to General Anaesthesia for Laparoscopic Abdominoperineal Rectal Amputation - Antunes, Marisa; Baumgärtel, Aleksander Johannes; Gjessing, Petter Fosse; Ytrebø, Lars Marius Giske (Journal of Pain Research, 2023)
Background: Spinal anaesthesia as an adjunct to general anaesthesia may reduce postoperative pain and opioid consumption after laparoscopic abdominoperineal rectal amputation. We designed a randomized double blinded pilot study with two objectives: 1) to explore potential benefits of spinal anaesthesia as an adjunct to general anaesthesia and 2) to provide power and sample size estimations for potential differences between the groups. Primary outcome measures were postoperative pain and oral morphine equivalent (OMEq) consumption. Methods: Patients scheduled for elective laparoscopic abdominoperineal rectal amputation at the University Hospital of North Norway were randomised to spinal (n=5) or a sham spinal procedure (n=5). Numeric rating scale (NRS) and OMEq were monitored postoperatively for 72 h. Results: Age, sex, body mass index, and ASA were not significantly different between the groups. During surgery, patients in the spinal group received less remifentanil (p=0.06). NRS was lower in the spinal group 1 hr after admittance to the post-anaesthesia care unit (PACU) (p=0.06) and on the first postoperative day at 8 AM (p=0.03). OMEq consumption in the PACU was lower in the spinal group (p=0.008), but no differences between the groups were detected after discharge to the ward. Sample size estimations revealed that eight patients in each group would be needed to study potential NRS differences after admission to the PACU and 23 patients in each group to study potential differences in OMEq consumption on day 1. Conclusion: Spinal anaesthesia as an adjunct to general anaesthesia reduces postoperative pain and opioid consumption after laparoscopic abdominoperineal rectal amputation. Data from the current study should be followed up by a sufficiently powered randomized controlled trial.